2020
DOI: 10.7150/jca.34423
|View full text |Cite
|
Sign up to set email alerts
|

p62 Suppressed VK3-induced Oxidative Damage Through Keap1/Nrf2 Pathway In Human Ovarian Cancer Cells

Abstract: Imbalance of redox homeostasis may be responsible for the resistance of cancer to chemotherapy. Currently, increasing studies demonstrated that vitamin K3 (VK3), which promoted the production of ROS, had potential to be developed as an anti-tumor agent. We found SKOV3/DDP cells with high levels of p62 were insensitive to VK3 compared with SKOV3 cells. Furthermore, Nrf2 downstream antioxidant genes such as HO-1(heme oxygenase 1) and NQO1 (NAD (P) H: quinone oxidoreductase 1) were upregulated in SKOV3/DDP cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Mitochondrial ROS signalling is also considered a valuable target since the imbalance between ROS production and ROS detoxification constitutes the pivotal molecular route contributing to aberrant proliferation and tumour cell survival in several types of cancer. Vitamin K3 (VK3) has the potential to be developed as an antitumour agent since it induces apoptosis by increasing the generation of ROS in ovarian cancer cells [111] . However, many cancer cells benefit from mROS generation through its effects on redox signalling; thus, refined strategies that allow for the specific modulation of mROS must be conceived.…”
Section: Mitochondria As Promising Targets For Cancer Therapymentioning
confidence: 99%
“…Mitochondrial ROS signalling is also considered a valuable target since the imbalance between ROS production and ROS detoxification constitutes the pivotal molecular route contributing to aberrant proliferation and tumour cell survival in several types of cancer. Vitamin K3 (VK3) has the potential to be developed as an antitumour agent since it induces apoptosis by increasing the generation of ROS in ovarian cancer cells [111] . However, many cancer cells benefit from mROS generation through its effects on redox signalling; thus, refined strategies that allow for the specific modulation of mROS must be conceived.…”
Section: Mitochondria As Promising Targets For Cancer Therapymentioning
confidence: 99%
“…Recent studies have reported that Nrf2 could be activated by AMP-activated protein kinase (AMPK) and modulate autophagy-related genes (e.g., p62, Beclin, and LC3B-1/2) to participate in the alleviation of oxidative stress in mammalian cells [ 22 ]. Autophagy-related protein p62 can inhibit Nrf2 degradation and promote Nrf2 stability and nuclear translocation by interfering with Keap1-Nrf2 interaction to participate in the cellular antioxidative stress response [ 23 ]. However, whether ZnLA could protect against oxidative stress by modulating AMPK-Nrf2 activation and autophagy signals is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear factor E2-related factor 2 (Nrf2) is a key transcription factor involving in maintaining cell redox homeostasis 89 , and HO-1 is one of the most important regulatory products. It is a bZIP transcription factor 10 . Under resting conditions, Nrf2 binds to kelch-like ECH-related protein 1 (keap1) and form a Keap1-Nrf2 complex 90 .…”
Section: Regulation Mechanism Of Ho-1 Expressionmentioning
confidence: 99%
“…The complex will be degraded by ubiquitous proteasome and exist in the cytoplasm in an inactive state. However, oxidative stress induces the modification of cysteine ​​residues in Keap1, causing Nrf2 to dissociate from the complex and increase the translocation of nucleus 10 . Within the nucleus, it binds to the antioxidant-responsive element (ARE) in target gene promoters and form the Nrf2-ARE signaling pathway 90 , activating the transcription of its downstream target genes, such as HO-1 and NADPH quinone dehydrogenase 1 (NQO1), protecting cells from oxidative damage and participating in maintaining redox homeostasis 24 , 42 , 56 .…”
Section: Regulation Mechanism Of Ho-1 Expressionmentioning
confidence: 99%